Development of Student Worksheets Based on Science Process Skills on Human Excretion System Materials - Lisa, Erma; Suryani, Ira; Tambunan, Efrida Pima Sari (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Development of Student Worksheets (LKPD) based on science process skills on human excretory system material presented in the form of an application on a smartphone which contains human excretion system material, stages of practicum activities and questions adapted to indicators of science process skills, which are expected to be able to train participants' thinking abilities educate. The research aims to find out: (1) the feasibility of developing science process skills-based LKPD (Student Worksheets): (2) the practicality of developing process skills-based LKPD (Student Worksheets); and (3) The effectiveness of developing LKPD (Student Worksheets) based on science process skills on human excretory system material. The development model in this study is 4D which consists of 4 stages, namely define, design, development, and disseminate the research subject of 30 students of class XI IPA MAS 12 Perbaungan. The research instruments are validation sheets for material experts, linguists, and media experts on feasibility testing, practitioner validation sheets to determine practicality, pretest and posttest sheets for effectiveness testing. The results of this study prove that the skill-based LKPD science process developed is declared very feasible with a percentage of 89.39%, very practical with a percentage of 81.94% and very effective with a high category of learning improvement that has been tested with n-gain with a score of 0.73 and excellent student response with a percentage of 81.58%. The results of this study prove that the developed science process skills-based learner worksheets are very feasible, very practical, and very effective to use in the learning process